HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA MAHASISWA PUTERI PENJASKESREK SEMESTER 3 UNIVERSITAS RIAU - Hengki Setiyadi Waruwu; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: this research starts from the observation of the researchers conducted on college student in lectures of Athletics especially long jump is still very low. In the implementation of particular courses of lectures in the Department of Sports Education Athletics University of Riau, a student is required to have an explosive limb muscles are good and have the ability to carry out a combination of long jump technique movement and gain good results anyway. The aim in this study was to examine the relationship explosive power leg muscle with long jump results in a student squat style princess Penjaskesrek Semester 3University of Riau. Population in this study were students Puteri Penjaskesrek Riau University Semester 3 years from 2013 to 2014 as many as 13 people. Sampling techniques in using total sampling technique, in which the entire population be made in the sample. Data obtained from measurements of the standing broad jump and long jump ability. Data were analyzed by using correlation produc moment. Based on the results of research and data processing using statistical procedures of research, it can be concluded that for the relationship between the variable x to the variable y obtained value of r = 0.863 then rxy> rtabel namely (0.863> 0.576), then Ho is rejected Ha accepted. Conclusion The hypothesis is accepted at significant level = 0.05, in other words there is a significant relationship between the explosive power leg muscle with a long jump results in student daughter Penjaskesrek 3.Keywords: Explosive Muscle Power Legs, long jump